Educating citizens : international perspectives on civic values and school choice - Wolf, Patrick J.; Macedo, Stephen, 1957- (Book collections on Project MUSE., 2004)
The United States is in the midst of historic experiments with publicly funded choice in K-12 education, experiments that recently received a 'green light' from the Supreme Court. Other countries have long experience with the funding and regulation of nonpublic schools. What is the US hoping to learn from these experiences?